IMPLEMENTATION OF WEB-BASED WORK PROGRAM SUBMISSION THROUGH THE LOCAL GOVERNMENT INFORMATION SYSTEM (SIPD) WEB IN NGAMPELSARI VILLAGE - Yuanita, Nabilla Ananda; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of web-based work program submissions through the Regional Government Information System (SIPD) in Ngampelsari Village, Sidoarjo Regency, with a focus on the effectiveness of SIPD in supporting transparency, accountability, and smoothness of the village development planning process and evaluating the obstacles faced by village governments. Method: This study uses a descriptive qualitative approach with data collection techniques through interviews with village officials (Kaur Planning) and documentation of the 2025 APBDes, which is then analyzed using George C. Edward III's policy implementation theory with four main indicators, namely communication, resources, disposition, and bureaucratic structure. Results: The results of the study show that the implementation of SIPD in Ngampelsari Village is still not running optimally, as can be seen from communication constraints regarding authority between villages and districts which caused some proposals to be rejected, limited human resources who control SIPD (only two people out of seven village apparatus) and lack of training, the disposition of village officials which although committed is still limited to administrative and does not touch the aspect of public transparency.  as well as weak bureaucratic structures due to the absence of SOPs, irregular cross-level coordination, and dependence on district instructions. Novelty: This research makes a new contribution by presenting empirical data on the use of SIPD at the village level through the framework of Edward III's theory comprehensively, which shows the complex interaction between communication, resources, disposition, and bureaucratic structure in the implementation of digital policies in villages, and can be a reference for the development of village governance digitalization policies in other regions.